ULU MUDA FOREST: IN THE PERSPECTIVE OF WATER CATCHMENT MANAGEMENT (Journal of Governance and Development (JGD), 2022)
Malaysia receives abundant rainfall averaging 3,000 mm annually that contributes to the continuous water resources to the country.However, issues arise on how to manage water supplies effectively and how to sustain the availability of clean water despite otherindustrial activities. Looking at the northern region of Malaysia, the 160,000 hectare of Ulu Muda in Kedah is the largest water catchment area that face the same issue. Even though Kedah is not facing any major issues on water resources since it has adequate catchment area, but the given situation of deforestation or logging activities at the area of the forest will someday bring effect on the water supplies to Kedah, Pulau Pinang and Perlis. This paper aims to address the issue together with measuring the water management system in Kedah.